KSF of family business - Boroš, Petr; Tyll, Ladislav; Machek, Ondřej, 1985-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2015)
Family business is a business in which family members have a large stake in ownership and also a deciding vote on business operation. This thesis deals with what makes the family businesses thriving. The research is conducted using the Good to Great framework by Jim Collins. Based mainly on quantitative and qualitative survey of 8 Czech companies of various fields and sizes, it was discovered that there are some links between the companies' success. These findings yield a set of recommendations, which is provided in the last chapter.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses